Critical tissue concentration of zinc in short duration mungbean (Vigna radiata) - VENKATESH, M S; HAZRA, K K; GHOSH, P K (The Indian Journal of Agricultural Sciences, 2014)
It could be concluded from the above study that growth pattern of short duration mungbean [Vigna radiata (L.) Wilczek] significantly influenced tissue Zn concentration at different stages. Plant tissue Zn concentration was moderate to highly correlated with dry matter production throughout the crop growth stages. Based on the quadratic relationship with dry matter production, the critical concentration of tissue Zn was higher (35.0 to 40.5 mg/kg) at early stage (30 DAS) which was reduced at 45 DAS (21.6 to 21.9 mg/kg). Considerable variation was also observed in critical Zn concentration with leaf position. Based on the variability of Zn concentration in plant tissues and relation with dry matter production, young fully expanded leaf at 45 DAS was found to be the efficient sampling plant part for the plant diagnostics of zinc. While, the optimum Zn dose for summer mungbean was quantified 14.5 mg/kg soil.